Sociological Analysis of Contemporary Youth Movements: the Strenghts of Classical Leadership Theories - N V Andrievskaya (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2011)
The article is devoted to the study of youth socio-political movements in terms of leadership theories. The author examines the development of leadership theories and provides the analysis of the activities of two youth organization's leaders in the context of the theories involved. In order to analyze the efficiency of leadership the author highlights the qualities essential for an ideal leader of a youth organization and identifies the type of leadership style. Further on, the author considers how far each of the candidates answers the ideal leadership model description.